Magnetic resonance diffusion-tensor imaging metrics in High Grade Gliomas: Correlation with IDH1 gene status in WHO 2016 era. Issue 116 (July 2019) - Augelli, Raffaele; Ciceri, Elisa; Ghimenton, Claudio; Zoccatelli, Giada; Bucci, Alessandra; Nicolato, Antonio; Beltramello, Alberto; Pinna, Giampietro; Ricciardi, Giuseppe K.
Highlights: IDH mutation is an important genetic marker in natural history of gliomas (WHO 2016). DTI metrics can help to analyze IDH1 mutation status in HGG. RD and MD can help to discriminate between HGG IDH1 wild-type and HGG IDH1 mutated. Abstract: Purpose: To evaluate any possible correlation between the presence of Isocitrate DeHydrogenase 1 mutation (IDH1m) and specific DTI (Diffusion Tensor Imaging) metrics, such as Fractional Anisotropy (FA), Mean Diffusivity (MD), Radial Diffusivity (RD) and Axial Diffusivity (AD). Methods: We retrospectively analyzed 47 patients who underwent an advanced-MR study with DTI followed by surgical intervention with a subsequent histologic diagnosis of High-Grade Glioma (HGG) and immunohistochemical evaluation of IDH1 (Isocitrate DeHydrogenase) mutation status. For each DTI metrics we measured the ratio between tumor and normal tissue and we evaluated the correlation with IDH1 mutation. Results: We observed a positive correlation with IDH1 status and RD and MD data. No correlation was demonstrated between IDH1 status and FA and AD. Discussion: Our results support the hypothesis that the number of residual axonal fibers, extracellular matrix composition and the presence of colliquated tissue, may together contribute to a global RD increase in HGG, with a relatively higher increase in IDH1m tumors. Conclusions: Our data are in favor of a need for multimodal advance evaluation of HGG. DTI metrics help to analyze IDH1 mutation status, in order to better characterize the lesions and to tailor treatment and follow up.